Assessment of Sustainability in Architecture Using The Modification of The Greenship Tools Model (Case Study of Mohammad Hatta Building of Universitas Islam Indonesia - Heyder Ahmed; Sugini Sugini (Departement of Architecture, Universitas Islam Indonesia, 2020)
Sustainable development is development that can meet the needs of the present without reducing the ability of future generations to meet their own needs. Educational institutions have an important role in shaping the human character and the future of the world to implement sustainability systems. The Mohammad Hatta UII building is the object of study in research aimed at finding out how much the value of sustainability is applied in development and becomes information for the reader. Now there is an assessment tool that works to assess how high a building's sustainability value is. Green Building Council Indonesia (GBCI) with Greenship Tools was chosen to be an assessment tool to determine the level of sustainability contained in the object of study by modifying some of the criteria therein. In the assessment process the highest results were obtained in the Appropriate Site Development category where all available points were met, while the Water Conservation category did not get any points at all and the Building Environmental Management category was eliminated in the evaluation aspect. The results of the sustainability calculation based on Greenship criteria from the modified Greenship Existing Building assessment type on the study object obtained 52.94%. To increase points in the assessment will be given several recommendations in the form of design concepts that are expected to be used as a reference in improving facilities to support the value of sustainability in the object of study.Keywords: assessment, development, Greenship, sustainability